Indonesian Adaptation of the Cultural Intelligence Scale (CQS) - Rikumahu, Marchya Carina Exaudy; Rahayu, Maria Nugraheni Mardi (Universitas Ahmad Dahlan, 2025)
Indonesia is a country with diverse cultural backgrounds, so intercultural interactions often occur. This research aims to adapt the Cultural Quotient Scale developed by Ang and Van Dyne (2008) into Indonesian to support various research on cultural intelligence. The CQS measuring tool consists of 20 statement items and is divided into 4-factors, namely metacognitive, cognitive, motivational, and behavioral. Testing was carried out using the Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) methods involving 324 Satya Wacana Christian University students who were divided into 2 random sample groups (EFA, n=162 & CFA, n=162). The results of this research indicate that the 4-factor structure of the 17 items of the Indonesian version of the CQS statement has a